Case Report: 43-years old-Male with Pulmonary Sequestration which Mimics Lung Tumor and Aspergillosis - Rumaratu, Simon Petrus Hardiyanto; Setyawan, Ungky Agus; Wardhana, Koernia Kusuma; Erawati, Dini Rachma; Yudhanto, Hendy Setyo (Malang Respiratory Journal, 2022)
Background: Pulmonary sequestration is a very rare congenital abnormality of the lung, which was responsible for 0.15-6.4% of all cases of congenital lung formation disorders. Pulmonary sequestration is often seen as recurrent pneumonia, accompanied by complaints of chest pain, shortness of breath and hemoptysis. Conventional angiography is the gold standard for diagnosing pulmonary sequestration and for demonstrating arterial supply and venous drainage. The optimal therapy for pulmonary sequestration is operative resection to avoid infection and damage to the lung parenchyma. Case Report: We reported a case of 43-years old-male with pulmonary sequestration, previously diagnosed with a lung tumor with massive left pleural effusion and pneumonia. A series of diagnostic tests found no malignant cells. During FNAB with CT scan guiding, we found an image of a fungus ball, thus, he was diagnosed with Aspergillosis. The patient was planned to undergo VATS. There were complications during the operation, thus, a lobectomy with an open thoracotomy was performed, and an arterial anomaly was found from the abdominal aorta. The operation was successful and the patient was able to carry on with his normal activities.Conclusion: Establishing a definite diagnosis of pulmonary sequestration is very difficult, and in this case, it was done through lobectomy with thoracotomy and through a multidisciplinary approach.